Flow equations for Yang-Mills theories in general axial gauges - Litim, Daniel F.; Pawlowski, Jan M. (Physics letters, 1999)
We present a formulation of non-Abelian gauge theories in general axial gauges using a Wilsonian (or 'Exact') Renormalisation Group. No 'spurious' propagator divergencies are encountered in contrast to standard perturbation theory. Modified Ward identities, compatible with the flow equation, ensure gauge invariance of physical Green functions. The axial gauge nA=0 is shown to be a fixed point under the flow equation. Possible non-perturbative approximation schemes and further applications are outlined.